Tanshinone IIA protects dopaminergic neurons against 6-hydroxydopamine-induced neurotoxicity through miR-153/NF-E2-related factor 2/antioxidant response element signaling pathway. (10th September 2015) - Zhang, X.S.; Ha, S.; Wang, X.L.; Shi, Y.L.; Duan, S.S.; Li, Z.A.
Highlights: Tan IIA protects against 6-OHDA neurotoxicity in SH-SY5Y cells. Tan IIA protects SH-SY5Y cells against 6-OHDA-induced apoptosis. Tan IIA attenuates 6-OHDA neurotoxicity in an Nrf2-dependent manner. Tan IIA reduced the elevated expression of miR-153 by 6-OHDA. Tan IIA protects against neurodegeneration of dopaminergic neurons in in vivo 6-OHDA model of Parkinson's disease. Abstract: Parkinson's disease (PD) is the second most common progressive neurodegenerative disorder with increased oxidative stress, the underlying vital process contributing to cell death. Tanshinone IIA (Tan IIA), a major bioactive diterpene quinone of Salva miltiorrhiza, had been proved effective in the MPTP model through its anti-inflammatory activity. Here in this research, we found that Tan IIA prevented the loss of nigrostriatal dopaminergic neurons by activating the NF-E2-related factor 2 (Nrf2)–antioxidant response element (ARE) pathway. The cytotoxicity of 6-hydroxydopamine (6-OHDA) was attenuated by the treatment of Tan IIA in SH-SY5Y cells, which significantly reduced 6-OHDA-induced lactic dehydrogenase release and reactive oxygen species production. Further study indicated that Tan IIA contributed to the nuclear accumulation of Nrf2, which bound to the ARE sequence, and activated ARE-regulated genes, including heme oxygenase-1, glutamate cysteine ligase catalytic subunit (GCLC) and glutamate cysteine ligase modifier subunit (GCLM). Tan IIA also protected against damage to mitochondrial membrane potential, reduced the translocation of cytochrome c from the mitochondria to the cytoplasm and the activation of Caspase-9 and Caspase-3. Moreover, we demonstrated the above effects were performed in Nrf2-dependent manner. Further studies revealed that Tan IIA reduced the enhancement of miR-153 by 6-OHDA, which targeted the 3′-UTR of Nrf2, and suppressed its expression and activation. Additionally, neurodegeneration caused by in vivo stereotaxic injection of 6-OHDA could also be ameliorated by the administration of Tan IIA. Taken together, our results strongly suggest that Tan IIA may be beneficial for the treatment of PD, and also confirm that targeting the Nrf2/ARE pathway is a promising strategy for therapeutic intervention in PD.